Analisis Etos Kerja terhadap Pengasuh di Pondok Pesantren Al Maufi - Hanifah, Lia; Hidayatulloh, Hafiz; Alfarizi, Ricko Sedes; Fitrianana, Aniqotuzzuhro’ (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
The purpose of this study was to analyze the relationship between work ethic and caregivers at Al-Maufi Islamic Boarding School. This study aims to find out how caregivers apply the Islamic work ethic in the Islamic boarding school. This type of research is a qualitative descriptive research method, namely research procedures using observation, interview and documentation methods. Based on the results of the interviews he had conducted with the caretaker of the Al-Maufi Islamic Boarding School, he explained that the work ethic, especially in a Islamic boarding school, is very important. Even though there is a transition or change in management, both sons and daughters, this does not change a rule in the pesantren. It can be concluded that the leadership of the Al-Maufi Islamic boarding school has a good work ethic, in terms of discipline, the leadership of the Islamic boarding school is very concerned about time, all the activities of the students are well organized. In addition, from an exemplary perspective, the leadership of the Islamic boarding school can provide a good example or uswah for the students.